2019
DOI: 10.1093/nar/gkz866
|View full text |Cite
|
Sign up to set email alerts
|

Modifying a covarying protein–DNA interaction changes substrate preference of a site-specific endonuclease

Abstract: Identifying and validating intermolecular covariation between proteins and their DNA-binding sites can provide insights into mechanisms that regulate selectivity and starting points for engineering new specificity. LAGLIDADG homing endonucleases (meganucleases) can be engineered to bind non-native target sites for gene-editing applications, but not all redesigns successfully reprogram specificity. To gain a global overview of residues that influence meganuclease specificity, we used information theory to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Adding additional layers of complexity to the engineering process are the observations that (1) for many LAGLIDADG protein-DNA complexes, overall binding affinity is dominated by formation of contacts across half of the protein-DNA interface (Thyme et al, 2009), (2) that distal mutations can unexpectedly alter specificity elsewhere in the protein-DNA interface (Laforet et al 2019), and (3) that a frequently observed amino acid substitution in the LA-GLIDADG protein family (corresponding to E178D in I-OnuI) that increases tolerance for (and activity against) target sites with altered central base pairs (McMurrough et al, 2018;Takeuchi et al, 2011) is a key element in the engineering process.…”
Section: Discussionmentioning
confidence: 99%
“…Adding additional layers of complexity to the engineering process are the observations that (1) for many LAGLIDADG protein-DNA complexes, overall binding affinity is dominated by formation of contacts across half of the protein-DNA interface (Thyme et al, 2009), (2) that distal mutations can unexpectedly alter specificity elsewhere in the protein-DNA interface (Laforet et al 2019), and (3) that a frequently observed amino acid substitution in the LA-GLIDADG protein family (corresponding to E178D in I-OnuI) that increases tolerance for (and activity against) target sites with altered central base pairs (McMurrough et al, 2018;Takeuchi et al, 2011) is a key element in the engineering process.…”
Section: Discussionmentioning
confidence: 99%
“…Primers were ordered from Integrated DNA Technologies. Wild-type I-OnuI was previously cloned between the NcoI and NotI sites in pProEX-HT-a (Invitrogen and Life Technologies) and pEndo backbone ( 38 , 39 ).…”
Section: Methodsmentioning
confidence: 99%
“…Meganucleases (MegNs) rely on the length of the target sequence and the structure of the DNA contact surface to specifically, accurately, and effectively identify the target. The mechanism of DNA recognition by MegNs involves binding patterns of protein side chains and nucleotide bases [ 15 ], deformation of groove dimensions, electrostatic distribution of the molecular surface, and additional contacts within and near the minor groove [ 16 ]. Binding affinity and cleavage activity sometimes have different efficiencies.…”
Section: Superiority Of Pscs and Gene Editing For Precision Medicine And Therapymentioning
confidence: 99%